TOTAL CHOLESTEROL AND C-REACTIVE PROTEIN LEVELS AS A PROGNOSTIC MARKERS OF UROSEPSIS - wahyudi, septa surya; Hardjowijoto, Sunaryo; Soebadi, Doddy M; Soetojo, Soetojo; Djojodimedjo, Tarmono; Budiono, Budiono (Indonesian Journal of Urology, 2016)
Objective: To investigate whether total cholesterol and C-reactive protein levels could be use as a prognostic factor for outcome in patients with urosepsis. Material & Methods: An analytic observational study using 30 patients assigned for total cholesterol and CRP level at the day of admission, three days later, and on the last day of sepsis or on the dead day. All subjects were managed according to standard urosepsis therapy. At the 14th day of treatment, patients were evaluated with a clinical severity score. Then we classified the outcome as improve/good condition, worse, and died. The variables were statistically tested using Spearman’s rho test with software SPSS 20. P < 0.05 was consider significant. Result: From 30 subjects with urosepsis, we found 15 patients in septic condition, 14 patients had severe sepsis and one patient had septic shock. The mean of total cholesterol level in patient with died and worse was lower than that in patient with good outcome. Day-1 (63.25 mg/dl and 101.38 mg/dl vs 119.5 mg/dl), day-3 (56.0 mg/dl and 93.6 mg/dl vs 128.6 mg/dl) and last day/died day (51.0 mg/dl and 82.25 mg/dl vs 154.8 mg/dl). The mean of CRP level in patient with died and worse was higher than that in patient with good outcome. Day-1 (177.18 mg/l and 146.74 mg/l vs 88.1 mg/l), day 3 (127.1 mg/l and 148.8 mg/l vs 56.2 mg/l) and last day/died day (141.88 mg/l and 88.71 mg/l vs 31.58 mg/l). These were statistically significant between total cholesterol and CRP levels in determining the outcome of urosepsis patient. Day-1 (p 0.000 vs 0.011), day-3 (p 0.000 vs 0.002), and last day/died day (p 0.000 vs 0.000). The coefficient correlation total cholesterol was better than CRP in day-1 (rho -0.633 vs 0.459), day-3 (rho -0.755 vs 0.543), and last day/died day (rho -0.874 vs 0.686). Conclusion: Low total cholesterol and high C-reactive protein levels can be used as poor prognostic in urosepsis patients. Total cholesterol level was better than CRP as a prognostic marker.